2003
DOI: 10.1007/s101200300008
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma occurring in the residual stomach following gastrectomy: plus discussion based on the literature in Japan

Abstract: A 53-year-old man was examined because of mild anemia (hemoglobin [Hb], 11.6g/dl) in August 1996. He had undergone pyloric gastrectomy with Billroth-I reconstruction for perforated benign gastric ulcer in 1988. Gastric transillumination and endoscopy showed comparatively soft, giant fold-like protruding lesions spreading over the entire residual stomach, and biopsy revealed the lesions to be malignant lymphoma. X-Rays of the large intestine and colonoscopy with biopsy demonstrated Borrmann type 2 highly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Il semble que lorsque le lymphome gastrique se greffe sur un moignon de gastrectomie, il s'agit souvent d'un lymphome à grandes cellules B de haut grade de malignité [9][10][11][12][13][14]. Ce type de tumeurs, caractérisées par leur chimiosensibilité, sont traitées par une polychimiothérapie associant, en plus du rituximab, la doxorubicine, le cyclophosphamide, la vincristine et le prednisone et par une éradication systématique de l'HP [15].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Il semble que lorsque le lymphome gastrique se greffe sur un moignon de gastrectomie, il s'agit souvent d'un lymphome à grandes cellules B de haut grade de malignité [9][10][11][12][13][14]. Ce type de tumeurs, caractérisées par leur chimiosensibilité, sont traitées par une polychimiothérapie associant, en plus du rituximab, la doxorubicine, le cyclophosphamide, la vincristine et le prednisone et par une éradication systématique de l'HP [15].…”
Section: Discussionunclassified
“…Selon les cas rapportés dans la littérature du lymphome malin survenant sur gastrectomie, il semble que son pronostic soit fluctuant [9,10,[12][13][14].…”
Section: Discussionunclassified
“…4 Lymphomas have been described in the proximal gastric stump 5 to 43 years after partial gastrectomy, with 15 cases reported in the western literature and 27 cases in Japan. 5,6 The gastric stump and the distal gastric segment may share in common an increased exposure to duodenal reflux with accompanying mucosal inflammation. It has been suggested that lymphocyte infiltration associated with chronic inflammation of the mucosa could develop into lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas have been described in the proximal gastric stump 5 to 43 years after partial gastrectomy, with 15 cases reported in the Western literature and 27 cases in Japan. 25,26 The proximal gastric stump after the partial gastrectomy and the distal gastric remnant after RYGBP may share in common an increased exposure to duodenal reflux with accompanying mucosal inflammation. It has been suggested that lymphocyte infiltration associated with chronic inflammation of the mucosa could develop into lymphoma.…”
Section: Gastric Cancer In the Bypassed Stomach After Gastric Bypassmentioning
confidence: 99%